Water and Bromide Recovery in Wick and Pan Lysimeters under Conventional and Zero Tillage - Schmidt, J.P; Lin, H (Communications in soil science and plant analysis, 2008)
Quantifying in situ solute transport through soils and the landscape has been widely acknowledged as important and yet challenging. The objective of this study was to evaluate water and bromide movement in no-tilled (NT) and conventionally tilled (CT) corn using two different types of in situ lysimeters - pan and capillary wick - for single rainfall events. Four zero-tension pan and four capillary-wick lysimeters were installed 1.2 m deep on opposite sides of four soil pits. Two were under NT corn, and two were under CT corn. Bromide (Br) was either surface applied or applied with an initial 25 to 27 mm of irrigation (33 to 34 g Br m²). A total of 120 to 147 mm of irrigation was applied continuously at 8.8 mm h⁻¹. Leachate was collected on 15 min intervals for 24 h and on greater intervals for up to 350 h. Lysimeter discharge and Br concentration were determined for each interval. After drainage began and until rainfall was discontinued, the water drainage rate was, on average, greater in NT (7.2 mm h⁻¹) than in CT (5.6 mm h⁻¹) based on results from the pan lysimeters. By contrast, the water drainage rate for the wick lysimeters was, on average, greater in CT (7.3 mm h⁻¹) than in NT (3.0 mm h⁻¹). The wick lysimeter appears to have behaved as a sink under the CT conditions, likely representing water flow in smaller channels. Under NT conditions, greater discharge observed with the pan lysimeter implicates the response from larger channels as the conduit for water flow. Flow-weighted mean Br concentration was less when Br was applied on the soil surface (17.9 mg L⁻¹) than when Br was applied with the irrigation water (50.6 mg L⁻¹). Implications from preferential flow studies are often determined based on a single method of evaluation for solute transport, which are likely subject to the limitation of the method used. This study illustrates that contrary to the conventional understanding about preferential flow in NT, water flow and Br transport to the 1.2-m depth was as great as or greater with CT than with NT based on the results from the wick lysimeters for single rainfall events.